Enhanced degree of polymerization of methacrylate and epoxy resins by plasmonic heating of embedded silver nanoparticles - Asmussen, Silvana Valeria (2015)
Silver nanoparticles (Ag NPs) were synthesized in situ in light-cured methacrylate and epoxy resins. The UV–vis spectra of the colloidal suspensions displayed an intense surface plasmon resonance band in the wavelength range 350–550 nm with an absorption peak at 415 nm. Suspensions containing different amounts of Ag NPs were photopolymerized by UV irradiation. Cylindrical specimens of the resulting nanocomposites (10-mm diameter × 1-mm thickness) were irradiated with a 420-nm LED source while the temperature evolution was monitored. The heat released by the Ag NPs under irradiation at the plasmon-resonant wavelength increases the temperature of the surrounding medium. The temperature reached in a methacrylate-based nanocomposite containing 0.03 wt% Ag NPs was 100 °C after 250 s irradiation. This increases the mobility of the reaction environment and, consequently, induces the polymerization of the unreacted monomer. Moreover, the degree of polymerization of films prepared from an epoxy resin containing 0.02 wt% Ag NPs was 35%, and then increased up to 75% after 10 min irradiation at 420 nm. In practice, the post-curing of partially cured polymers is commonly carried out by thermal treatments. Results obtained in this study show that the use of a small amount of Ag NPs, as controlled sources of heat under light irradiation, is an attractive strategy to post cure methacrylate and epoxy resins in the absence of external heating.